Comparison of Pathogenicity of Different Infectious Doses of H3N2 Canine Influenza Virus in Dogs - Liu, Yongbo; Fu, Cheng; Lu, Gang; Luo, Jie; Ye, Shaotang; Ou, Jiajun; Wang, Xiangbin; Xu, Haibin; Huang, Ji; Wu, Liyan; Zhang, Xin; Wu, Peixin; et al. (Frontiers in Veterinary Science, 2020)
The canine influenza virus (CIV) outbreaks raised concerns due to threats to health of dogs. The successful construction of a canine influenza (CI) infection model is essential to study the CIV. Here we investigated the pathogenicity of different infectious doses of H3N2 CIV in Beagle dogs. Thirty-seven healthy Beagle dogs were used in the experiment, which have been infected with dose of 103, 104, 105, and 106 EID50. Compared to the other three groups, when the infected dose was 106 EID50, dogs presented obvious clinical symptoms, high virus titer, and typical pathological changes. Considering the ensemble of clinical scores, body temperature, virus shedding, lung lesions, pathological section scores, and visceral virus titers, we determined that 106 EID50 is the minimum infectious dose for Beagles infection model. These results indicate that 106 EID50 is the minimum infectious dose of H3N2 CIV that can cause obvious clinical manifestations and pathological changes of CI in Beagle dogs. However, the other three infectious doses of dogs have almost no clinical symptoms. The theoretical framework developed in this research will guide the establishment of a infection model of CIV and future research.